Mengenal Kaum Pentakosta - Nepho Gerson Laoly (STT Injili Indonesia Medan, 2020)
Abstract: This article was created to increase understanding of the Pentecostal group. The research was conducted with literature research that talked about the Pentecostals. This article discusses the history of the development of the Pentecostal group, how this group developed with the house church, the fundamentalist label given to Pentecostals, and how this group uses the Bible as a guide for their daily life.Keywords: Pentecost ; Fundamentalist ; House Church; Bible Abstrak:Artikel ini dibuat agar pemahaman akan kelompok Pentakosta semakin meningkat. Penelitian dilakukan dengan riset literatur yang membicarakan kaum Pentakosta. Artikel ini membicarakan bagaimana sejarah perkembangan kelompok Pentakosta, bagaimana kelompok ini berkembang dengan gereja rumah, label fundamentalis yang diberikan kepada kaum Pentakosta, dan bagaimana kelompok ini mempergunakan Alkitab sebagai pedoman hidup keseharian. Kata Kunci: Pentakosta ; Fundamentalis ; Gereja Rumah; Alkitab